2020
DOI: 10.3846/est.2019.11950
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Mechanical Properties and Structure of Anhydrite Binder Modified by Ultra-Dispersed Siltstone

Abstract: This research is devoted to modification of physical and mechanical properties and structure of a binder based on natural anhydrite. A sedimentary rock siltstone was added into the composition as a mineral ultrafine additive. The presence of aluminosilicate minerals proves that finely ground siltstone can be used as a mineral additive in the composition of the anhydrite binder, accelerating crystallization of gypsum new formations and densifying the structure of gypsum stone. For the first time, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Crystalline particles of ground quartz sand act as centers of crystallization of new formations. This is confirmed by comparing the results obtained by other authors, for example, Tokarev et al [46].…”
Section: Figure 5 Demonstrates High Rheological and Strength Characteristics Of The Developed Composite Binderssupporting
confidence: 89%
See 1 more Smart Citation
“…Crystalline particles of ground quartz sand act as centers of crystallization of new formations. This is confirmed by comparing the results obtained by other authors, for example, Tokarev et al [46].…”
Section: Figure 5 Demonstrates High Rheological and Strength Characteristics Of The Developed Composite Binderssupporting
confidence: 89%
“…Crystalline particles of ground quartz sand act as centers of crystallization of new formations. This is confirmed by comparing the results obtained by other authors, for example, Tokarev et al [46]. There is an increase in strength of more than 60% at a cement substitution level of more than 40%.…”
Section: Figure 5 Demonstrates High Rheological and Strength Characteristics Of The Developed Composite Binderssupporting
confidence: 86%
“…7). The experimental results showed higher values compared both to natural and thermal anhydrite 26,27 …”
Section: Resultsmentioning
confidence: 86%
“…The experimental results showed higher values compared both to natural and thermal anhydrite. 26,27 The presented strength indicators showed that the selected types of additives contributed to the activation of the material synthesized at 45 °C (with a lamellar form of crystals) but did not activate the anhydrite obtained at 25 °C. This can lead to the conclusion that, depending on the structure, shape, and size of the crystals, the same additives-activators act differently on the material.…”
Section: Binders Based On Synthesized Anhydritementioning
confidence: 99%